Identification of Rpv3 and Rpv12 loci in the progenies of the ‘Talisman’ grape cultivar - E. T. Ilnitskaya; M. V. Makarkina; T. D. Kozina; E. A. Kozhevnikov; V. S. Petrov (Труды по прикладной ботанике, генетике и селекции)
Currently, when implementing breeding programs to produce pathogen-resistant grape genotypes, the DNA marker assessment method is used both directly in breeding-oriented selection and in evaluation of the initial gene pool. The ‘Talisman’ grape cultivar, with its fine consumer characteristics, resistance to diseases and frost, and a functionally female type of flower, is promising for breeding.We performed a DNA marker assessment of the ‘Talisman’ genotype and cultivars as well as new hybrids of grapes developed with the participation of cv. ‘Talisman’ for the presence of the Rpv3 and Rpv12 downy mildew resistance loci. It is known that the presence of these two genes in the same grape genotype has an additive effect. According to the pedigree of cv. ‘Talisman’ (Frumoasa Albe × Vostorg), the presence of these genes can be assumed in the studied sample. The study was based on PCR with an analysis of the results on an automatic genetic analyzer. DNA was isolated from young shoots of the analyzed plants by the CTAB method. We used closely linked microsatellite markers recommended for DNA identification of the allelic status of the Rpv3 (UDV305, UDV737) and Rpv12 (UDV343, UDV360) genes. The simultaneous presence of Rpv3 and Rpv12 was detected only in the cv. ‘Talisman’ genotype. When analyzing the progeny genotypes of cv. ‘Talisman’, the presence of the Rpv3 downy mildew resistance gene was found in the grape hybrids “Agat Dubovskiy”, “Pestry”, and Rpv12 gene in the ‘Viktor’ and ‘Preobrazheniye’ genotypes. DNA-marker analysis confirmed the prospects of the cv. ‘Talisman’ genotype for breeding of table cultivars as a donor of the downy mildew resistance genes Rpv3 and Rpv12.